ANALISIS KANDUNGAN LOGAM TIMBAL (Pb) DAN LAJU KONSUMSI AMAN KERANG KEPAH (Polymesoda erosa) DI SUNGAI DONAN CILACAP - Amazonia Dhita Risanti; Suratman Suratman; Agnes Fitria Widiyanto (Kesmas Indonesia, 2013)
ABSTRACT One of the content that contained in Donan River is known as a lead (Pb). Lead that contained in the water will accumulate in the body of water organisme, one of which is the body shells (Polymesoda erosa). This type of research is a descriptive study and use the test "one sample t test". Based on the results of research on three stations in the River Donan is in the vicinity of Tritih Kulon, around the industrial area and around the Port Crossing Sleko, indicate that the sample (Polymesoda erosa) examined showed a significant difference to the standard used, SNI No. 7387 Year of 2009. The results of analysis using the "one-sample t test" indicates p value at stations I is 0,028, station II is 0,031 and 0,034 for station III, where a significance value less than 0,05 which indicates there is a significant difference between Pb content in the body of shells in River Donan with standard that used. The results of the calculation of the rate of consumption is safe for the shellfish mussel in the River Donan at station I that is equal to 0.00372 kg/day, the station II of 0.00367 kg/day and station III of 0.0037 kg/day. For the public should not consume mussel shells (Polymesoda erosa) from River Donan Cilacap in quantities of more than 0.004 grams/day to avoid the accumulation of Pb in the body. Keyword: Metal Content of Lead (Pb), flesh shells (Polymesoda erosa), The Rate of Safe Consumption Kesmasindo, Volume 6, Nomor 2, Juli 2013, Hal 85-93